Política externa brasileira e América Latina: possibilidades para a construção de uma liderança brasileira regional - Santos, Natalia Liberato Dos [UNIFESP] (2019)
Since the post-independece period, the Brazilian foreign policy has sought to maintais certain traditions around its policies, one of which is the search for a greater role and regional leadership. Whether trought the diversification of partners or through the approach of main poles of power, the role of a greater prominence and leadership was sought. The main debates around this objective have focused on Brazil´s national capacities to play such a role and on the limitations and adaptations that the nation would have to make in order to achieve it. In this research we debate the possibilities that the diversification of instruments, in this case trought the Latin American identity, can brin to Brazil. In order to sustain the debate around the identity factor, together with the Braziliand forein policy theme, we bring a survey of Public Opinion resulting from an academic partnership with seven other Latin American countries.